A Novel High-Order Symplectic Compact FDTD Schemes for Optical Waveguide Simulation - Xiaojing Kuang; Zhixiang Huang; Ming Fang; Qi Qi; Mingshen Chen; Xianliang Wu (IEEE Photonics Journal, 2022)
As a 2-D full-wave numerical algorithm in the time domain, the compact Finite Difference Time Domain (FDTD) is an efficient algorithm for eigenvalue analysis of optical waveguide system. However, the numerical dispersion accuracy and stability of fast algorithm need to be improved while simulating at high frequency. A novel high-order symplectic compact FDTD scheme is developed and validated for optical waveguide modal analysis. The stability condition and the numerical dispersion of schemes with fourth-order accuracy in temporal and spatial using the symplectic integrator and compact scheme are analyzed. By comparisons with other time-domain schemes, their stable and accurate performance is qualitatively verified. The proposed high-order SC-FDTD method can be used for efficiently simulating electrically large and longitudinally invariant optical devices since the reduction of simulation dimensionality and the novel high-order symplectic algorithm can greatly reduce the memory cost and the numerical dispersive errors.